Leveraging National Cancer Institute Programmatic Collaboration for Uterine Cervix Cancer Brachytherapy in Puerto Rico After Hurricane Maria - Kunos, Charles A.; Ivy, Percy (Frontiers in Oncology, 2019)
Evaluating the impact of natural disasters on cancer patients is vital to the recovery of cancer treatment services and infrastructure. In September 2017, Hurricane Maria demolished the gynecologic cancer service in the United States territory of Puerto Rico and its outreach to the territory of the Virgin Islands of the United States. Patient access to brachytherapy for uterine cervix cancer patients can be difficult to measure in the aftermath of a hurricane. The United States National Cancer Institute (NCI) surveyed gynecologic radiation medicine providers on the island to generate an independent perspective on gynecologic brachytherapy service recovery after the hurricane. Providers were asked about patient displacement, infrastructure loss, and reestablishment of cancer treatment. Here, the NCI provides its perspective on recovery of these services as it relates to its pre-hurricane investment for staff in the NCI Community Oncology Research Program.